Inhibition of NOX4/ROS Suppresses Neuronal and Blood-Brain Barrier Injury by Attenuating Oxidative Stress After Intracerebral Hemorrhage - Xie, Jiayu; Hong, Enhui; Ding, Baiyun; Jiang, Weiping; Zheng, Shizhong; Xie, Zhichong; Tian, Dan; Chen, Yizhao (Frontiers in Cellular Neuroscience, 2020)
Intracerebral hemorrhage (ICH) is a common and severe neurological disorder that can effectively induce oxidative stress responses. NADPH oxidase 4 (NOX4) is a member of the NOX family of oxidases. It is expressed in the brain normally and involved in cell signal transduction and the removal of harmful substances. In some pathological conditions, it mediates inflammation and the aging of cells. However, few studies have focused on whether NOX4 is involved in brain injury caused by ICH. Therefore, this study aimed to clarify the role of NOX4 in the pathological process that occurs after ICH and the potential mechanism underlying its role. An ICH rat model was established by the injection of collagenase IV, and the expression of NOX4 was then determined. Further, siRNA-mediated protein expression knockdown technology was used for NOX4 knockdown, and western immunoblotting, immunohistochemistry, immunofluorescence, enzyme-linked immunosorbent assay (ELISA), and other molecular biological techniques were used to assess the effects of NOX4 knockdown. Neurobiological scoring, brain water content determination, and other brain injury detection methods were also performed to assess the role of NOX4 following ICH. We found that the expression of NOX4 increased in the brains of rats after ICH, and that it was mainly expressed in neurons, astrocytes, and vascular endothelial cells. After knocking down NOX4, the level of oxidative stress in the brain was considerably decreased, the neurobehavioral scores and apoptosis of neurons were significantly alleviated, and the impairment of blood-brain barrier function in rats following ICH was significantly improved. In conclusion, this study suggests that NOX4 expression is upregulated after ICH, which may cause an imbalance in the oxidative stress of relevant cells in the brain, leading to subsequent apoptosis of neurons and damage to the blood-brain barrier from SBI following ICH.